2017
DOI: 10.1177/0300060516682882
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatment with midazolam on etomidate-induced myoclonus: A meta-analysis

Abstract: ObjectiveTo investigate the effect of pretreatment with midazolam on myoclonus induced by etomidate injection.MethodsA meta-analysis was performed using Review Manager software, version 5.2. Two researchers independently searched PubMed, Cochrane Library, and Embase® databases for randomized controlled trials involving patients who underwent etomidate induced general anaesthesia with or without midazolam pretreatment, published between 1990 and 2016. Outcome measures comprised overall myoclonus incidence rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 16 publications
3
38
0
Order By: Relevance
“…Myoclonus is one of the common adverse reactions of etomidate, which can result in serious consequence in patients with poor cardiovascular reserve. 33 , 34 In our study, the incidence of myoclonus in group E was nearly 30%, which was similar to the rate reported by Liu et al 7 On the contrary, myoclonus occurred in only two people in either the low-dose RT group or the high-dose RT group. Additionally, the severity of myoclonus were also reduced in the group LR and group HR than that in the etomidate group.…”
Section: Discussionsupporting
confidence: 90%
“…Myoclonus is one of the common adverse reactions of etomidate, which can result in serious consequence in patients with poor cardiovascular reserve. 33 , 34 In our study, the incidence of myoclonus in group E was nearly 30%, which was similar to the rate reported by Liu et al 7 On the contrary, myoclonus occurred in only two people in either the low-dose RT group or the high-dose RT group. Additionally, the severity of myoclonus were also reduced in the group LR and group HR than that in the etomidate group.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, patients in the propofol group experienced more fluctuations when vital signs changes were observed over time. Myoclonus occurred in 12% of patients in the etomidate group; this is consistent with a study that showed that midazolam premedication reduced myoclonus compared to that reported by a previous etomidate/remifentanil study 30,31. In addition, for this double-blinded study, we initially used 0.1 mg/kg of etomidate, which was slightly less than the usual single dose of etomidate (0.15–0.20 mg/kg) 32.…”
Section: Discussionsupporting
confidence: 88%
“…In patients suffering from trauma or presenting for ophthalmic surgery due to open globe injury, myoclonus will further increase intraocular pressures and may result in vitreous prolapse. 6 Despite the fact that etomidate is frequently used for unstable patients, the physiological impact of myoclonus can negate the otherwise beneficial effects of etomidate administration in these patients. 7 Methods to reduce the impact of myoclonus in patients given etomidate have been proposed.…”
Section: Introductionmentioning
confidence: 99%